2017
DOI: 10.1080/09553002.2017.1325025
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy enhanced the radioresistance of non-small cell lung cancer by regulating ROS level under hypoxia condition

Abstract: We elucidated the possible mechanisms of autophagy in regulating cancer cell death or survival. These results supply a new opinion about the intrinsic factor of radioresistance of hypoxia tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Furthermore, autophagy preserves damaged organelles, including mitochondria [ 54 ]. In many cases, autophagy can reduce the rate of DNA damage-induced apoptosis, playing a protective role in tumor cells, which induces radioresistance in tumor cells [ 57 , 58 ]. Targeting autophagy can be an effective way to improve the effects of radiotherapy [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, autophagy preserves damaged organelles, including mitochondria [ 54 ]. In many cases, autophagy can reduce the rate of DNA damage-induced apoptosis, playing a protective role in tumor cells, which induces radioresistance in tumor cells [ 57 , 58 ]. Targeting autophagy can be an effective way to improve the effects of radiotherapy [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…High expression levels of HIF-1α have been reported to be associated not only with radiation resistance, but also with a poor prognosis of patients with lung cancer ( 20 23 ). Shibamoto et al reported that the administration of a HIF-1 inhibitor, in adjunction with radiation, significantly suppressed the proliferation of lung cancer cell lines in vivo ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is crucial for the management of unresectable esophageal carcinoma, but radioresistance of the tumor is a hindrance to achieving sustained remission or long-term survival. Autophagy has been reported to enhance the radioresistance of non-small-cell lung cancer ( 9 11 ). Preliminary studies indicated that autophagy inhibition improved the radiosensitivity of breast cancer and esophageal SCC, consequently enhancing the cytotoxicity of radiotherapy ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%